Visual Communication in Prehistoric Public Spaces: A Linguistic Landscape Study of Liangkabori Cave - Risman Iye; Dian B; Nur Haizah Aopmonaim; Fithriyah Indah Nur Abida; Susiati (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background: Linguistic landscape studies have predominantly focused on written texts in contemporary public spaces. This study extends the concept of Semiotic Landscapes to pre-literate contexts by examining the pictograms of Liangkabori Cave in Muna as a form of prehistoric public communication. This study aims to analyze how the pictograms in Liangkabori Cave function as elements of a prehistoric semiotic landscape that convey visual communication and social meaning. Methodology: This qualitative study applies a visual semiotics approach integrated with archaeological analysis. Data were obtained from hematite-based pictograms, supported by 3D scanning and spectroscopic analysis to examine painting techniques on karst surfaces. Findings: The pictograms appear to serve both informational and symbolic functions. Hunting and boat motifs suggest representations of subsistence strategies and maritime orientation. The kite motif may indicate an understanding of basic aerodynamic principles and communal practices, while the sun symbol can be interpreted as reflecting cosmological beliefs. These findings are interpretive and do not directly represent verifiable historical intentions. Conclusion:  Liangkabori Cave can be understood as a form of prehistoric visual communication system. The findings suggest that visual representations were likely used to convey ecological knowledge, maritime practices, and belief systems. However, these interpretations remain tentative and highlight the importance of further interdisciplinary research and conservation efforts. Originality:  This study contributes to linguistic landscape research by extending its scope to prehistoric contexts and proposing rock art as a form of semiotic landscape in pre-literate societies.